1979
DOI: 10.1177/014662167900300110
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Measurement of Unpleasant Events and Relations with Depression

Abstract: The goal was to construct a psychometrically sound instrument for the measurement of aversive events. Hypotheses about the occurrence of aversive events and depression were also tested. The Unthe first version consisted of the number of events that had occurred. Subsequently, weights were assigned to each item based on ratings by a sample of judges (Holmes & Rahe, 1967). The judges were asked to rate the life events as to the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
90
3

Year Published

1980
1980
2011
2011

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 147 publications
(98 citation statements)
references
References 25 publications
5
90
3
Order By: Relevance
“…These material concerns may lead to preoccupations with security that inhibit the spontaneity necessary for an active social life. These findings are consistent with the literature on the outlooks of depressed persons and their social relationships (Coyne, 1976;Lewinsohn & Talkington, 1979).…”
Section: Discussionsupporting
confidence: 92%
“…These material concerns may lead to preoccupations with security that inhibit the spontaneity necessary for an active social life. These findings are consistent with the literature on the outlooks of depressed persons and their social relationships (Coyne, 1976;Lewinsohn & Talkington, 1979).…”
Section: Discussionsupporting
confidence: 92%
“…Pearlin and Schooler (1978) conducted a study of people ''engaged in very ordinary-indeed, required-pursuits'' (p. 123). Lewinsohn and Talkington (1979) constructed a 320-item daily unpleasant events scale.…”
Section: The Micro Level: Daily Hassles and Upliftsmentioning
confidence: 99%
“…For example, Kanner et al (1981) reported that an aggregated measure of daily hassles was a significant predictor of subsequent symptom levels. Like-wise, Lewinsohn and Talkington (1979) reported that unpleasant daily events experienced during the previous month were related moderately to depression symptomatology. Finally, DeLongis et at.…”
Section: Analytic Approaches To the Study Of Daily Eventsmentioning
confidence: 99%